ChemInform Abstract: Melanogenesis‐Modulating Diketopiperazine Derivatives from Hypocrea spp. Issue 19 (18th April 2013) - Kawabata, Tetsuro; Uchida, Chiaki; Kato, Hikaru; Tsubata, Tomoyuki; Takano, Fumihide; Ohta, Tomihisa
Abstract Among a series of known compounds, a new dioxopiperazine, hypocreasin (I), is isolated from the fungus Hypocrea spp.